2020
DOI: 10.3390/ijms21041188
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting FGF21 Inhibits Retinal Vascular Leakage in In Vivo and In Vitro Models

Abstract: The aim of the current study was to investigate the impact of long-acting fibroblast growth factor 21 (FGF21) on retinal vascular leakage utilizing machine learning and to clarify the mechanism underlying the protection. To assess the effect on retinal vascular leakage, C57BL/6J mice were pre-treated with long-acting FGF21 analog or vehicle (Phosphate Buffered Saline; PBS) intraperitoneally (i.p.) before induction of retinal vascular leakage with intravitreal injection of mouse (m) vascular endothelial growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…However, we do not exclude the potential contribution of local FGF21. Moreover, vascular protective effects of FGF21 on the retinal endothelial cells [ 16 ], systemic metabolic changes by pemafibrate administration, and direct protective effects of pemafibrate on the retina [ 57 ] could also be taken into consideration, which needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we do not exclude the potential contribution of local FGF21. Moreover, vascular protective effects of FGF21 on the retinal endothelial cells [ 16 ], systemic metabolic changes by pemafibrate administration, and direct protective effects of pemafibrate on the retina [ 57 ] could also be taken into consideration, which needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…In the retina, long-acting FGF21 (PF-05231023) was reported to decrease pathological retinal vessel proliferation and promote physiological retinal vascularization in a murine oxygen-induced retinopathy model [ 14 ] and protect against retinal neural dysfunction in a type 1 diabetic mouse model [ 15 ]. Furthermore, our previous study showed that long-acting FGF21 prevented retinal vascular leakage induced by VEGF in vitro and in vivo [ 16 ]. The administration of FGF21 has therapeutic effects on lipid and glucose metabolism in mice.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they indicated that long-acting FGF21 maintained retinal function in a streptozotocin-induced diabetic mouse model using electroretinography analyses [ 124 ]. Furthermore, we reported that long-acting FGF21 reduced retinal vascular leakage in vivo and in vitro via maintenance of claudin-1 expression [ 125 ]. In that study, we also detected expressions of FGFR1 and β-Klotho in human endothelial cells [ 125 ], which implies that the same strategy regarding the therapeutic role of FGF21 may also be applicable to humans.…”
Section: Functions Of Spparmα In the Eyementioning
confidence: 99%
“…Furthermore, we reported that long-acting FGF21 reduced retinal vascular leakage in vivo and in vitro via maintenance of claudin-1 expression [ 125 ]. In that study, we also detected expressions of FGFR1 and β-Klotho in human endothelial cells [ 125 ], which implies that the same strategy regarding the therapeutic role of FGF21 may also be applicable to humans. Retinal vascular leakage is seen in the early stage of DR patients [ 3 , 126 ].…”
Section: Functions Of Spparmα In the Eyementioning
confidence: 99%
“…Whole-mounted retinas were imaged using confocal microscopy (LSM 880; Zeiss, Oberkochen, Germany). The fluorescence intensity of FITC-dextran was analyzed with Zeiss microscope software ZEN Intellesis to segment and quantify vascular leakage from retinal vessels based on previous protocols ( 60 ). Retinas were costained with Alexa Fluor 594–conjugated isolectin GS-IB 4 (Thermo Fisher Scientific; I21413).…”
Section: Methodsmentioning
confidence: 99%